2012
DOI: 10.1186/cc11382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: Probiotics in critical care

Abstract: Patients in ICUs represent a relatively small subgroup of hospitalised patients, but they account for approximately 25% of all hospital infections. Approximately 30% of ICU patients suffer from infection as a complication of critical illness, which increases the length of ICU stay, morbidity, mortality and cost. Gram-negative bacteria are the predominant cause of ICU-related infections and with the rise in multidrug-resistant strains we should focus our attention on nonantibiotic strategies in the prevention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 89 publications
0
14
0
3
Order By: Relevance
“…22 Probiotics are defined as live microorganisms that when administered in adequate amounts may confer health benefits on people with specific illnesses. 23 Animal research and in vitro studies 24 have shown that probiotics improve gut barrier function, 25,26 inhibit gut colonization with pathogenic bacteria, 27 improve colonization with healthy commensals, 28,29 protect from enteropathogenic infection through production of acetate, 30 enhance innate immunity, 31 and increase maturation of the enteric nervous system, 32 all of which have the potential to decrease the risk of LOS in preterm infants. However, the recent Cochrane Review 33 (2014) 34 (2015) also reported similar results on LOS (RR, 0.919; 95% CI, 0.823-1.027; P = .137; 17 randomized controlled trials [RCTs], N = 5215).…”
mentioning
confidence: 99%
“…22 Probiotics are defined as live microorganisms that when administered in adequate amounts may confer health benefits on people with specific illnesses. 23 Animal research and in vitro studies 24 have shown that probiotics improve gut barrier function, 25,26 inhibit gut colonization with pathogenic bacteria, 27 improve colonization with healthy commensals, 28,29 protect from enteropathogenic infection through production of acetate, 30 enhance innate immunity, 31 and increase maturation of the enteric nervous system, 32 all of which have the potential to decrease the risk of LOS in preterm infants. However, the recent Cochrane Review 33 (2014) 34 (2015) also reported similar results on LOS (RR, 0.919; 95% CI, 0.823-1.027; P = .137; 17 randomized controlled trials [RCTs], N = 5215).…”
mentioning
confidence: 99%
“…7,8 Kondisi inflamasi yang meluas akibat infeksi bakteri terbukti meningkatkan lama perawatan (length of stay), biaya perawatan, morbiditas, dan mortalitas pasien. 9 Upaya pencegahan dibutuhkan agar kondisi infeksi tidak meluas dan berkembang menjadi sepsis, serta menjaga agar parameter hematologi pasien tetap normal, yaitu dengan meningkatkan sistem kekebalan tubuh atau imunitas pasien. Salah satu upaya meningkatkan imunitas adalah dengan pemberian bakteri asam laktat (BAL) yang di isolasi menjadi probiotik.…”
Section: Pendahuluanunclassified
“…у 2010 р. [9] та результатами інших дослідників [3,7,8], внутрішнє застосування пре-і пробіотиків вважається обгрунтованим (табл.1; 2; 3). Рекомендації з інших клінічних і доклінічних питань із застосування пробіотиків Рекомендації 1.Початкова доза для ДДМТ: 1,5 × 109 КУО / добу до досягнення ентерального харчування 50-60 мл / кг /добу.…”
Section: вступunclassified